Identification and distribution of new candidate T6SS effectors encoded in Salmonella Pathogenicity Island 6 - Blondel, Carlos J.; Amaya, Fernando A.; Bustamante, Paloma; Santiviago, Carlos A.; Pezoa, David (Frontiers in Microbiology, 2023)
The type VI secretion system (T6SS) is a contact-dependent contractile multiprotein apparatus widely distributed in Gram-negative bacteria. These systems can deliver different effector proteins into target bacterial and/or eukaryotic cells, contributing to the environmental fitness and virulence of many bacterial pathogens. Salmonella harbors five different T6SSs encoded in different genomic islands. The T6SS encoded in Salmonella Pathogenicity Island 6 (SPI-6) contributes to Salmonella competition with the host microbiota and its interaction with infected host cells. Despite its relevance, information regarding the total number of effector proteins encoded within SPI-6 and its distribution among different Salmonella enterica serotypes is limited. In this work, we performed bioinformatic and comparative genomics analyses of the SPI-6 T6SS gene cluster to expand our knowledge regarding the T6SS effector repertoire and the global distribution of these effectors in Salmonella. The analysis of a curated dataset of 60 Salmonella enterica genomes from the Secret6 database revealed the presence of 23 new putative T6SS effector/immunity protein (E/I) modules. These effectors were concentrated in the variable regions 1 to 3 (VR1-3) of the SPI-6 T6SS gene cluster. VR1-2 were enriched in candidate effectors with predicted peptidoglycan hydrolase activity, while VR3 was enriched in candidate effectors of the Rhs family with C-terminal extensions with predicted DNase, RNase, deaminase, or ADP-ribosyltransferase activity. A global analysis of known and candidate effector proteins in Salmonella enterica genomes from the NCBI database revealed that T6SS effector proteins are differentially distributed among Salmonella serotypes. While some effectors are present in over 200 serotypes, others are found in less than a dozen. A hierarchical clustering analysis identified Salmonella serotypes with distinct profiles of T6SS effectors and candidate effectors, highlighting the diversity of T6SS effector repertoires in Salmonella enterica. The existence of different repertoires of effector proteins suggests that different effector protein combinations may have a differential impact on the environmental fitness and pathogenic potential of these strains.